FAKTOR FAKTOR YANG MEMPENGARUHI AUDIT DELAY PADA PENYAMPAIAN LAPORAN KEUANGAN TAHUN 2018-2020 - Praskananta, Resa Ega; Astuti , Puji (Universitas Nusantara PGRI Kediri, 2022)
The goal of this study was to find out how profitability, company size, and the reputation of KAP affect audit delays in metal and related industrial companies listed on the Indonesia Stock Exchange from 2018 to 2020. Utilizing SPSS version 28's logistic regression analysis technique, test your hypothesis. This research approach employs a sample with the intention of gathering samples and also applies quantitative methods. Firm size and KAP reputation have positive effects on audit delay that are sometimes small and sometimes big. Profitability has a positive effect on audit delay that is sometimes big and sometimes small, and profitability, company size, and reputation all have big positive effects on audit delay at the same time. This study demonstrates that a variety of variables can be used to quantify audit delay, but the reputation of the KAP has not been widely considered in previous studies.